Compulsory Testament: State Intervention in the Protection and Fulfillment of Human Rights of Non-Muslim Heirs - Rahman, Abdul; Lohalo, Georges Olemanu; Imširović, Mirela; Bin Paidi, Zulhilmi (LAW REFORM, 2024)
This article discusses the importance of state intervention in protecting and fulfilling the human rights of non-Muslim heirs through the institution of compulsory testament. In the diverse social landscape of Indonesian society, it is possible for one heir to adhere to a non-Muslim religion while the other two heirs are Muslim. This situation raises a legal problem in the field of inheritance, as the non-Muslim heir may risk losing their inheritance rights. Both religious rights and inheritance rights are human rights that must be protected, and their fulfillment must be guaranteed by the state through the establishment of policies regarding compulsory testament. This study employs a normative legal research method to examine existing regulations, the challenges faced by non-Muslim heirs, and the role of the state in promoting justice and protecting human rights. The results of the study conclude that mandatory wills intended for non-Muslim heirs are based on customary law with the principles of justice, social justice, and humanity. Mandatory wills for non-Muslim families also accommodate the democratic atmosphere in society and the state, answering the need for a sense of justice that is the right of every individual and preventing inequality in the pluralistic Indonesian society. It is necessary to strengthen regulations related to compulsory testament, to guarantee the rights of non-Muslim heirs, in order to create a more just and civilized society.